The Effect of Teaching Methods and Formal Reasoning Ability on Student Learning Outcomes - Sappaile, Baso Intang; Nuridayanti, Nuridayanti (Journal International Inspire Education Technology, 2024)
The purpose of this study is to examine the influence of teaching methods and formal reasoning abilities on students' learning outcomes. The research employs a quantitative research method and utilizes simple linear regression analysis with the assistance of SPSS version 16. Regression is a statistical technique used to analyze the relationship between one or more independent variables and a dependent variable. The population and sample size for this study consist of 50 students. The results of the research lead to the conclusion that the simple linear regression test yields a Sig. value of 0.001 < 0.05. Based on decision-making principles, it can be inferred that X1 and X2 have a simultaneous impact on the variable Y. Therefore, it can be concluded that both the teaching method (X1) and formal reasoning (X2) have an influence on the students' learning outcomes (Y). This finding further strengthens previous research findings by employing a better methodology and a larger sample size, demonstrating that formal reasoning affects learning outcomes, although there are still other factors that influence learning outcomes, such as motivation, environment, and so on.